Toys and the Portable Antiquities Scheme: A Source for Exploring Later Medieval Childhood in England and Wales. (3rd July 2018) - Harper, Emma
ABSTRACT: This article examines the contribution that can be made to discussions of the nature of childhood in the later medieval period (c. 1000–1600AD) through a study of artefacts recorded by the Portable Antiquities Scheme, a government funded initiative that encourages the voluntary recording of archaeological objects in England and Wales. Seventy-one objects recorded by the Scheme on its online database have been classified as later medieval 'toys' and these form the basis for the discussion here. Paying particular attention to the objects described as figures or dolls, these finds will be integrated with evidence from archaeological excavations, contemporary written and artistic sources, and theoretical discussions of the nature of childhood in the past. It will be argued these dolls are evidence for not only adults across society imposing particular behaviours upon children, but also of the direct agency of children in the material record.